When Giant Stick Insects Play With Colors: Molecular Phylogeny of the Achriopterini and Description of Two New Splendid Species (Phasmatodea: Achrioptera) From Madagascar - Glaw, Frank; Hawlitschek, Oliver; Dunz, Andreas; Goldberg, Julia; Bradler, Sven (Frontiers in Ecology and Evolution, 2019)
Achrioptera is a taxon of extremely large and exceptionally colorful stick insects endemic to Madagascar and the Comoros Archipelago. We study the phylogenetic position of the Achriopterini, comprising the genera Achrioptera and Glawiana, based on a multigene phylogeny and conclude that it is the sister group to other Madagascan phasmids (Anisacanthidae) rather than to Neotropical or Australo-Pacific groups as was suggested in a previous study based on morphology. Our results also point to unresolved relationships (potential paraphyly of Achrioptera), taxonomic issues (elevation of A. punctipes cliquennoisi to species level), and detection of cryptic diversity (in A. impennis), demonstrating the need of additional research. A DNA barcoding approach based on COI sequences of Achrioptera species revealed a clear discrimination between closely related and morphologically similar species. Applying integrative taxonomy using multiple lines of evidence we demonstrate that the well-known species with blue males from Montagne des Français and Foret d'Orangea in the far north of Madagascar, previously attributed to Achrioptera fallax, represents a new species, which we describe as Achrioptera manga sp. nov. based on morphological, chromatic, and genetic (mitochondrial and nuclear) differences. We also describe a second new giant species from this massif: Achrioptera maroloko sp. nov. is among the largest insects (females reaching up to 24 cm total length) and differs from its sister species A. spinosissima from western Madagascar in morphology, coloration, and substantial DNA barcode divergence. These magnificent new species confirm the significance of the Montagne des Français area as a hotspot of biodiversity and microendemism. The biogeographic pattern of the species pair A. fallax / A. manga is paralleled by species pairs of reptiles and amphibians suggesting a similar evolutionary history. Finally, we discuss the sexual dichromatism of Achrioptera species with conspicuous males and mostly cryptic females. As possible reasons, we consider female mate choice, divergent habits of males and females, reduced predation pressure, and aposematism due to accumulation of toxic substances.